2015
DOI: 10.1007/s11187-015-9658-9
|View full text |Cite
|
Sign up to set email alerts
|

R&D subsidies and productivity in SMEs

Abstract: This dissertation consists of an introductory chapter and four separate empirical studies which study higher education and productivity in Finland. Introductory chapter presents shortly the motivation, background and main results of this thesis. First three articles focus on the relationship between working while studying, dropout behavior and later labor market outcomes at individual level. Fourth article examines how subsidies affect labor productivity at the firm level.The first article of this thesis studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 167 publications
(171 reference statements)
1
35
0
Order By: Relevance
“…Looking at those, Dmirel et al (2012) and Piras et al (2012) indicated that R&D activities tended to be associated with company growth, further reflected in the higher survival rates (Lee et al, 2015). Karhunen et al (2015) provided evidence for a growth in employment among companies undertaking more R&D activities, and a number of other studies have indicated a positive association with output and productivity (Doraszelski et al, 2013;Hall et al, 2009).…”
Section: Investment Purposementioning
confidence: 97%
“…Looking at those, Dmirel et al (2012) and Piras et al (2012) indicated that R&D activities tended to be associated with company growth, further reflected in the higher survival rates (Lee et al, 2015). Karhunen et al (2015) provided evidence for a growth in employment among companies undertaking more R&D activities, and a number of other studies have indicated a positive association with output and productivity (Doraszelski et al, 2013;Hall et al, 2009).…”
Section: Investment Purposementioning
confidence: 97%
“…In the end, this profitability must come from a higher flow of revenues. However, Karhunen and Huovari (Karhunen & Huovari, 2015) show with data from Finland that labor productivity in SMEs seems not to be affected after a subsidy reception, even when this type of policies tends to increase the firms' human capital levels; also, Catozzella and Vivarelli (2011) show with data from Italy that innovation productivity tends to be reduced after subsidy; this could be a result of the innovation cost increase, but also because of the decrease of innovation revenues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, literature has begun to show the long-term effect of subsidies by finding there are greater effects in the long term than those estimated in the short term (Bodas-Freitas et al, 2017;Cin et al, 2017;G. Crespi et al, 2015;Engel et al, 2016;Guo et al, 2016;Howell, 2017;Karhunen & Huovari, 2015;Tello, 2015;Widmann, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fifth, firm size also matters although the evidence on this is ambiguous reflecting both selection criteria (which might be biased towards smaller firms) and larger firms' greater propensity to undertake innovation (Aerts and Schmidt 2008; Czarnitzki and Lopes-Bento 2013) 4 . Sixth, foreign-owned firms are less likely to receive public support (Aerts and Schmidt 2008;Czarnitzki and Lopes-Bento 2013) but there is some evidence that firms which are part of a wider enterprise group are more likely to receive public support (Karhunen and Huovari 2015). Finally, there is some evidence that the presence of R&D staff within an enterprise is also linked positively to the receipt of subsidies in smaller Finnish firms (Karhunen and Huovari 2015).…”
Section: Public Intervention To Support Randd and Innovationmentioning
confidence: 99%